Attitude toward Youth Suicide “Understanding the Mental Health Fraternity’s Perspective:” A Mixed Method Survey - Yogender Kumar Malik; Adwitiya Ray; Sujata Sethi; Rajiv Gupta (Indian Journal of Social Psychiatry)
Background: Suicide rates in India are rising, especially youth suicide. The most important role played by psychiatrists in the identification, prevention, and management of suicidal behavior. Aims: The study’s aim was to assess the attitudes of psychiatrists toward youth suicide. Methods: A cross-sectional, mixed-methods design was employed. Institutional Ethics Committee approval was obtained, and data were collected through online surveys distributed through Google Forms. A total of 113 mental health professionals participated. Quantitative data were analyzed using descriptive statistics, whereas qualitative responses were coded and thematically analyzed. Results: The study reveals that 95.6% of psychiatrists believe youth suicide can be prevented, with a strong consensus (89.4%) against the notion that once a young person decides to commit suicide, no one can stop them. Psychiatrists with a family history of suicide emphasize the importance of mental health professionals, crisis management, and social support in preventing and addressing suicide. Conclusions: The study emphasizes the role of psychiatrists in youth suicide prevention. Findings suggest a need for enhanced mental health education, accessible support services, and a comprehensive approach addressing societal and psychological factors. Future research should focus on deepening understanding and refining intervention strategies to effectively address youth suicide.